×

Close

Type:
**Note**Course:
**
Placement Preparation
**Specialization:
**Quantitative Aptitude**Offline Downloads:
**2**Views:
**20**Uploaded:
**30 days ago**Add to Favourite

The Chain Rule
mc-TY-chain-2009-1
A special rule, the chain rule, exists for differentiating a function of another function. This unit
illustrates this rule.
In order to master the techniques explained here it is vital that you undertake plenty of practice
exercises so that they become second nature.
After reading this text, and/or viewing the video tutorial on this topic, you should be able to:
• explain what is meant by a function of a function
• state the chain rule
• differentiate a function of a function
Contents
1. Introduction
2
2. A function of a function
2
3. The chain rule
2
4. Some examples involving trigonometric functions
4
5. A simple technique for differentiating directly
5
1
c

1. Introduction
In this unit we learn how to differentiate a ‘function of a function’. We first explain what is
meant by this term and then learn about the Chain Rule which is the technique used to perform
the differentiation.
2. A function of a function
Consider the expression cos x2 . Immediately we note that this is different from the straightforward
cosine function, cos x. We are finding the cosine of x2 , not simply the cosine of x. We call such
an expression a ‘function of a function’.
Suppose, in general, that we have two functions, f (x) and g(x). Then
y = f (g(x))
is a function of a function. In our case, the function f is the cosine function and the function g
is the square function. We could identify them more mathematically by saying that
g(x) = x2
f (x) = cos x
so that
f (g(x)) = f (x2 ) = cos x2
Now let’s have a look at another example. Suppose this time that f is the square function and
g is the cosine function. That is,
f (x) = x2
g(x) = cos x
then
f (g(x)) = f (cos x) = (cos x)2
We often write (cos x)2 as cos2 x. So cos2 x is also a function of a function.
In the following section we learn how to differentiate such a function.
3. The chain rule
dy
In order to differentiate a function of a function, y = f (g(x)), that is to find
, we need to do
dx
two things:
1.
Substitute u = g(x). This gives us
y = f (u)
Next we need to use a formula that is known as the Chain Rule.
2.
Chain Rule
dy
dy du
=
×
dx
du dx
2
c

Key Point
Chain rule:
To differentiate y = f (g(x)), let u = g(x). Then y = f (u) and
dy
dy du
=
×
dx
du dx
Example
Suppose we want to differentiate y = cos x2 .
Let u = x2 so that y = cos u.
It follows immediately that
The chain rule says
dy
= − sin u
du
du
= 2x
dx
dy du
dy
=
×
dx
du dx
and so
dy
= − sin u × 2x
dx
= −2x sin x2
Example
Suppose we want to differentiate y = cos2 x = (cos x)2 .
Let u = cos x so that y = u2
It follows that
Then
du
= − sin x
dx
dy
= 2u
du
dy
dy du
=
×
dx
du dx
= 2u × − sin x
= −2 cos x sin x
Example
Suppose we wish to differentiate y = (2x − 5)10 .
Now it might be tempting to say ‘surely we could just multiply out the brackets’. To multiply
out the brackets would take a long time and there are lots of opportunities for making mistakes.
So let us treat this as a function of a function.
3
c

Let u = 2x − 5 so that y = u10 . It follows that
du
=2
dx
Then
dy
= 10u9
du
dy
dy du
=
×
dx
du dx
= 10u9 × 2
= 20(2x − 5)9
4. Some examples involving trigonometric functions
In this section we consider a trigonometric example and develop it further to a more general
case.
Example
Suppose we wish to differentiate y = sin 5x.
Let u = 5x so that y = sin u. Differentiating
dy
= cos u
du
du
=5
dx
From the chain rule
dy du
dy
=
×
dx
du dx
= cos u × 5
= 5 cos 5x
Notice how the 5 has appeared at the front, - and it does so because the derivative of 5x was 5.
So the question is, could we do this with any number that appeared in front of the x, be it 5 or
6 or 12 , 0.5 or for that matter n ?
So let’s have a look at another example.
Example
Suppose we want to differentiate y = sin nx.
Let u = nx so that y = sin u. Differentiating
du
=n
dx
Quoting the formula again:
dy
= cos u
du
dy
dy du
=
×
dx
du dx
So
dy
= cos u × n
dx
= n cos nx
So the n’s have behaved in exactly the same way that the 5’s behaved in the previous example.
4
c

## Leave your Comments